2013
DOI: 10.1002/pola.26918
|View full text |Cite
|
Sign up to set email alerts
|

Renewable benzoxazine monomers from “lignin-like” naturally occurring phenolic derivatives

Abstract: The benzoxazines of three naturally occurring phenylpropanoid phenols: ferulic, coumaric, and phloretic acids, and their esters are described. Benzoxazines with conjugated unsaturated chains exhibit unusual poor thermal stability and degrade partially at the polymerization temperature making necessary the use of a catalyst (BF 3 .Et 2 O) to low the polymerization temperature and prevent degradation. Polybenzoxazines are prepared thermally and characterized by DSC and TGA techniques.The resulting materials have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 38 publications
3
69
0
Order By: Relevance
“…However, another reason for the higher T g of poly(MU‐a) compared to that of poly(U‐a) might be due to the presence of the methyl group in the repeating units, which increases the steric constraints toward molecular rearrangement and consequently impairing chain mobility resulting in a higher value of T g . Poly(PH‐a) shows the lowest value of the T g obtained in this study and is consistent with results previously reported in the literature . It has been documented that a higher cross‐linking in methyl cinnamate‐containing resins, with respect to the unsubstituted PH‐a , is due to additional cross‐linking sites, such as the extra CC double bond, as well as more possible cross‐linking reactions as the reported transesterification between ester groups and the –OH generated during polymerization of the benzoxazines …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…However, another reason for the higher T g of poly(MU‐a) compared to that of poly(U‐a) might be due to the presence of the methyl group in the repeating units, which increases the steric constraints toward molecular rearrangement and consequently impairing chain mobility resulting in a higher value of T g . Poly(PH‐a) shows the lowest value of the T g obtained in this study and is consistent with results previously reported in the literature . It has been documented that a higher cross‐linking in methyl cinnamate‐containing resins, with respect to the unsubstituted PH‐a , is due to additional cross‐linking sites, such as the extra CC double bond, as well as more possible cross‐linking reactions as the reported transesterification between ester groups and the –OH generated during polymerization of the benzoxazines …”
Section: Resultssupporting
confidence: 91%
“…Poly(PH‐a) shows the lowest value of the T g obtained in this study and is consistent with results previously reported in the literature . It has been documented that a higher cross‐linking in methyl cinnamate‐containing resins, with respect to the unsubstituted PH‐a , is due to additional cross‐linking sites, such as the extra CC double bond, as well as more possible cross‐linking reactions as the reported transesterification between ester groups and the –OH generated during polymerization of the benzoxazines …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As aromatic compounds including phenolic derivates are the second most abundant class of organic compounds in nature representing about 25% of the earth's biomass, quite a large number of renewable phenol derivatives have been tested in recent years to synthesize benzoxazine precursors such as diphenolic acid, cardanol, vanillin, eugenol, chavicol, guaiacol, “lignin‐like” naturally occurring phenolic compounds (coumaric acid, ferulic acid, and phloretic acid), umbelliferone, arbutin, urushiol, catechol, etc. A special interest is focused on difunctional benzoxazine structure because it leads to cross‐linking.…”
Section: Introductionmentioning
confidence: 99%
“…Another important feature of polybenzoxazines is the simple synthesis of their monomers. Basically, any suitable primary amine and phenolic compound could form 1,3-benzoxazine monomers with formaldehyde (Scheme 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The only possible drawback in monomer synthesis is the selection of functional groups on starting materials and solvent systems that suppress the reaction.…”
Section: Introductionmentioning
confidence: 99%